Dobro wspólne przesłanką współdziałania podmiotów publicznych i prywatnych w obszarze gospodarki komunalnej - Borkowski, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This study addresses legal issues concerning cooperation between local governmental authorities and private entrepreneurs in the field of fulfilling public tasks. Current regulations allow for transferring by way of cooperation certain municipal services tasks to external entities. The legal framework for the transfer is acivil law contract. The contracting parties are: alocal governmental body, being the entity responsible for and obligated to perform municipal services tasks, and a private entrepreneur conducting its business activity within the economic freedoms resulting from the constitutional principle of the free economic activity. Cooperation between public and private entities is an expression of atrend to optimise the provision of municipal services. The state, which is the guarantor of the proper fulfilment of public needs, is obligated to secure continuous supervision of the effects of privatising public tasks. The major factor in assessing the proper fulfilment of public needs is acategory of public welfare as an element of the common interest. At the same time the narrowly defined common interest constitutes afoundation for the arrangements that govern the performance of public tasks of local authorities together with private entrepreneurs, in accordance with the principles of mutual benefits and efficiency.
Keywords: gospodarka komunalna; podmioty publiczne; podmioty prywatne; wspóldziałanie; dobro wspólne